Smart concrete for thermal energy harvesting - Teo, Yong Fang (Nanyang Technological University, 2022)
Sustainability is an important goal in global to preserve environment for future. Green energy harvesting by using ambient sources would be an alternative power supply. Metakaolin-based geopolymer was reported as a better thermoelectric material as compared to Ordinary Portland concrete. Metakaolin-based geopolymer possess higher absolute thermoelectric power than Ordinary Portland concrete. The previous study discovered that conductive fibre is a good admixture to enhance thermoelectric properties of Ordinary Portland concrete. Moreover, previous research reported that thermoelectric properties of metakaolin geopolymer tends to be highly dependence on ions mobility. Hence, this study aims to explore the thermoelectric properties of metakaolin-based geopolymer with steel fibre content and metakaolin-based geopolymer with salt content. The thermoelectric behaviour is evaluated by thermoelectric figure of merit (ZT). Metakaolin-based geopolymer with 0.6 wt% steel fibre content possess a high Seebeck coefficient of 2860 μV/°C which is 1.8 times higher than normal metakaolin-based geopolymers. The addition of steel fibre was also reported to have positive effect on thermoelectric figure of merit (ZT). Therefore, metakaolin-based geopolymer with optimum content of 0.6 wt% of carbon has great potential to use as green energy harvesting material. However, there is no significant positive effect of thermoelectric effect in metakaolin-based geopolymer with salt content.